Kewenangan Mahkamah Agung dalam Upaya Hukum Peninjauan Kembali Sengketa Tata Usaha Negara pada Pemilihan Bupati dan Wakil Bupati Boalemo - Nisrina, Fathillah Fasya; Sofiani, Trianah (Manabia: Journal of Constitutional Law, 2024)
The implementation of elections as an embodiment of democracy is closely related to territorial structures at national, provincial, and autonomous district levels. The Supreme Court has the authority to resolve election administration violations, including decisions that cancel the participation of candidate pairs in regional head elections. The dispute over the election of the Boalemo Regent and Deputy Regent brought to the Supreme Court for judicial review raises questions about the Supreme Court's authority under Article 154 paragraph (10), which states that the final legal remedy is cassation. This research is normative juridical research using legislative, conceptual, and case approaches, with data collected from primary, secondary, and tertiary legal materials. Analysis is conducted after data is inventoried and systematized. The results show that Article 153 paragraph (10) of Law Number 10 of 2016 states that the Supreme Court's decisions are final and cannot be subject to judicial review. The decision of the Boalemo Regency Election Commission, which established a new candidate pair after the cassation decision, violates the principle of legal certainty. The Cassation Panel stated that the candidate pair eligible to participate in the 2017 Boalemo Regent and Deputy Regent Election was Rum Pagau and Lahmudin Hambali, according to the Decree of the Boalemo Regency Election Commission.